Centralised Chaining for Wireless Personal Area Network - R, Halesh M; Kottari, Chethan G; Ahamed, Jamaluddin; Rao, P Kedareshwar; Sandimani, Vinayak Y (Journal of ISMAC, 2024)
Centralised chaining represents a method of organizing and coordinating the communication and interaction among the nodes within the PAN. It aligns with the objective of developing a PAN protocol with high interference immunity and low radio noise. The proposed idea aims to optimize the interconnectivity of the PAN nodes, enabling seamless communication, sensing, actuation, and data transmission within the network. The need for high-quality data, that uses minimal power (1mW to 100mW) and long distances is increasing every day. Since ninety percent of devices are used internally, more bandwidth, low latency, high spectral efficiency, and high smooth output are needed. Additionally, as the user base expands, researchers face greater difficulty in creating a dependable and quick wireless communication system using these current gadgets. The proposed new design of the PAN is expected to overcome these issues with the help of advanced algorithms and protocols that improve the interconnectivity of the devices participating in the PAN.
Keywords: Personal Area Networks (PAN); IoT; Cloud; Communication Protocols